RBBP6‐Mediated ERRα Degradation Contributes to Mitochondrial Injury in Renal Tubular Cells in Diabetic Kidney Disease - Hongtu Hu; Jijia Hu; Zhaowei Chen; Keju Yang; Zijing Zhu; Yiqun Hao; Zongwei Zhang; Weiwei Li; Zhuan Peng; Yun Cao; Xiaoling Sun; Fangcheng Zhang; et al. (Advanced Science)
Abstract Diabetic Kidney Disease (DKD), a major precursor to end‐stage renal disease, involves mitochondrial dysfunction in proximal renal tubular cells (PTCs), contributing to its pathogenesis. Estrogen‐related receptor α (ERRα) is essential for mitochondrial integrity in PTCs, yet its regulation in DKD is poorly understood. This study investigates ERRα expression and its regulatory mechanisms in DKD, assessing its therapeutic potential. Using genetic, biochemical, and cellular approaches, ERRα expression Was examined in human DKD specimens and DKD mouse models. We identified the E3 ubiquitin ligase retinoblastoma binding protein 6 (RBBP6) as a regulator of ERRα, promoting its degradation through K48‐linked polyubiquitination at the K100 residue. This degradation pathway significantly contributed to mitochondrial injury in PTCs of DKD models. Notably, conditional ERRα overexpression or RBBP6 inhibition markedly reduced mitochondrial damage in diabetic mice, highlighting ERRα’s protective role in maintaining mitochondrial integrity. The interaction between RBBP6 and ERRα opens new therapeutic avenues, suggesting that modulating RBBP6‐ERRα interactions could be a strategy for preserving mitochondrial function and slowing DKD progression.